Science For the Layman [review of The Canon A Whirligig Tour of the Beautiful Basics of Science (Angier, N.; 2007)]. - Upson, S. (IEEE spectrum)
This ambitious, 304-page sprint through the fundamentals delivers its lessons via cheerful interviews with hundreds of top-notch scientists. However, the author's jittery style may alienate most people. The author, Natalie Angier, who reports on science for The New York Times, dips into physics, chemistry, and biology, and then on to rock formations and plants. She addresses the basic principles in each field, her chatty prose flipping between explanatory depth and comfortable imagery. Ultimately, the overlacking lack of focus robs readers of anything solid to clasp, and they are left itching for a more substantive narrative to connect the ample supply of colorful anecdotes. However, for those readers who are charmed by the Angier's freewheeling style, The Canon is one way to tickle the brain.